2016
DOI: 10.1590/0001-3765201620150574
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Portulaca oleracea extracts against 6-hydroxydopamine-induced lesion of dopaminergic neurons

Abstract: The Portulaca oleracea L. (Portulacaceae) is a cosmopolitan species with a wide range of biological activities, including antioxidant and neuroprotective actions. We investigated the effects of P. oleracea extracts in a 6-hydroxydopamine rat model of Parkinson's disease, a debilitating disorder without effective treatments. Chemical profiles of aqueous and ethanolic extracts of whole plant were analyzed by thin layer chromatography and the antioxidant activity was assessed by 2,2-diphenyl-1-picrilhidrazila met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Treating high-fat mice with purslane extracts reduced lipid peroxidation and increased activities of antioxidant enzymes in blood and liver [32]. Besides that, purslane exerted neuroprotective effects against some neurotoxins in 6-OHDA-induced rat model and rotenone-induced cellular and mouse models of PD [25]. In this study, purslane aqueous extract showed its high potential for PD treatment by improvements in PD-like phenotypes in the fly model with dUCH knockdown.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Treating high-fat mice with purslane extracts reduced lipid peroxidation and increased activities of antioxidant enzymes in blood and liver [32]. Besides that, purslane exerted neuroprotective effects against some neurotoxins in 6-OHDA-induced rat model and rotenone-induced cellular and mouse models of PD [25]. In this study, purslane aqueous extract showed its high potential for PD treatment by improvements in PD-like phenotypes in the fly model with dUCH knockdown.…”
Section: Discussionmentioning
confidence: 78%
“…Purslane was demonstrated to have protective effects in neurotoxin-induced models of PD. 6-OHDA-induced mice treated with purslane showed an improvement in motor ability after 15 days and a decrease in dopaminergic neuronal cell death after 4 weeks [25]. Oleracein E from purslane rescued rotenone-induced SH-SY5Y human neuroblastoma cells from apoptosis [26].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of pharmacological effects were shown for P. oleracea extracts, including antibacterial [10], hypolipidemic, anti-aging, anti-inflammatory [11,12], skeletal muscle relaxant [11,13], analgesic, wound healing [14], hypoglycemic [15], neuropharmacological [16], bronchodilatory [14,17], hypocholesterolemic [18], and antioxidant activities [15,19,20]. Other studies showed the importance of purslane consumption in the reduction of the occurrence of many diseases such as cancer [21,22] and heart disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic level of plasma oxalate has been associated with atherogenic activity through increasing the intracellular calcium concentration in endothelial cells and inhibition of endothelial proliferation (25). Although P. oleracea extract at the dose of 400 mg/kg has been used in some studies (26), but it seems that the lower doses would have the better safety profile with minor adverse effects. The results of the present study also showed increasing in weight loss after administration of P. oleracea seeds extract in dexamethasone-induced hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%